2020
DOI: 10.1038/s41419-019-2202-0
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β is a key regulator of the ROS-dependent necrotic death induced by the quinone DMNQ

Abstract: Signaling pathways controlling necrosis are still mysterious and debated. We applied a shRNA-based viability screen to identify critical elements of the necrotic response. We took advantage from a small molecule (G5) that makes covalent adducts with free thiols by Michael addition and elicits multiple stresses. In cells resistant to apoptosis, G5 triggers necrosis through the induction of protein unfolding, glutathione depletion, ER stress, proteasomal impairments, and cytoskeletal stress. The kinase GSK3β was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 72 publications
(109 reference statements)
1
15
0
Order By: Relevance
“…Notably, GSK3 activity was increased by ROS in multiple cell types, and this increase is important for ROS-induced cell death in damaged/injured tissue, including heart, neuron, and liver. [200][201][202][203][204] These studies provide some evidence for potential positive feedback between ROS and GSK3 that controls cell death (Figure 3).…”
Section: Gsk3 and Rosmentioning
confidence: 87%
“…Notably, GSK3 activity was increased by ROS in multiple cell types, and this increase is important for ROS-induced cell death in damaged/injured tissue, including heart, neuron, and liver. [200][201][202][203][204] These studies provide some evidence for potential positive feedback between ROS and GSK3 that controls cell death (Figure 3).…”
Section: Gsk3 and Rosmentioning
confidence: 87%
“…How these events integrate with classic apoptotic signaling is not clear. In some studies, induction of oxidative stress can be observed in the initial phases of proteotoxic stress [84,151,152]. Certainly, the augmented levels of ROS and calcium can be responsible for the induction of alternative forms of death in response to the proteotoxic stress observed in different studies [153,154].…”
Section: Additional Cell Death Responsesmentioning
confidence: 99%
“…As mentioned above, insulin resistance causes production of ROS via the activation of the AGE/RAGE pathway, inducing various stress sensitive signaling pathways, such as NF-κB, JNK/SAPK, p38 MAPK, and Akt pathway in particular ( Rains and Jain, 2011 ). Increased oxidative stress inactivates the Akt pathway, concomitantly to downstream activation of GSK3 and subsequent hyperphosphorylation of tau protein ( Bloch-Damti and Bashan, 2005 ; Hambright et al, 2015 ; Zhao et al, 2017 ; Ciotti et al, 2020 ).…”
Section: Insulin Resistance and Admentioning
confidence: 99%